Lymphodepletion in Cell Therapy - Paton, Eduardo José de Alencar; Duarte Barroso, Fernando (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2022)
Chimeric antigen receptor (CAR) T-cell therapy has become a factible therapy for hematologic neoplasms. Prior to infusion, strategies as lymphodepletion and bridge therapy are frequently performed to prolong the persistence of infused cells and increase the effectiveness of the treatment. The aim of this review is to investigate the use of Lymphodepletion and bridge therapy, protocols available, indications, advantages, negative effects, agent associated toxicity, applicability for specific onco-hematological diseases and how to optimize the procedure, guarantying security and efficacy of this approach.